PENGARUH PEMBELAJARAN AKIDAH AKHLAK DALAM MENGATASI PERILAKU VERBAL BULLYING PADA SISWA (Penelitian di MTs. Negeri 4 Sukabumi Waluran Kabupaten Sukabumi) - Gesti Agisna Yuniar; Mulyawan; Muhammad Syamsudin Nurfalah (Adisam Publisher, 2026)
This study is motivated by the persistence of verbal bullying among students despite the implementation of Aqidah Akhlak learning. The objective of this study is to examine the effect of Aqidah Akhlak learning on verbal bullying behavior among students at MTs Negeri 4 Sukabumi. This research employed a quantitative method with a survey approach. The population consisted of 251 students, with a sample of 72 respondents determined using the Slovin formula. Data were collected through questionnaires that had been tested for validity and reliability, supported by interviews. Data analysis was conducted using descriptive and inferential statistics. The results indicate that Aqidah Akhlak learning is categorized as strong, while verbal bullying behavior is categorized as low. Statistical testing shows that the F-count value of 49.78 is greater than the F-table value of 3.98, with a correlation coefficient of 0.645. This finding demonstrates a positive and significant effect of Aqidah Akhlak learning on reducing verbal bullying behavior, with a contribution level of 64.5%. Therefore, higher intensity of Aqidah Akhlak learning is associated with lower levels of verbal bullying behavior among students.